A 24 GHz Waveguide based Radar System using an Advanced Algorithm for I/Q Offset Cancelation - Will, Christoph; Linz, Sarah; Mann, Sebastian; Lurz, Fabian; Lindner, Stefan; Weigel, Robert; Kölpin, Alexander (Advances in Radio Science, 2017)
Precise position measurement with micrometer accuracy plays an important role in modern industrial applications. Herewith, a guided wave Six-Port interferometric radar system is presented. Due to limited matching and discontinuities in the radio frequency (RF) part of the system, the designers have to deal with DC offsets. The offset voltages in the baseband lead to worse relative modulation dynamics relating to the full scale range of the analog-to-digital converters and thus, considerably degrade the system performance. While common cancelation techniques try to estimate and extinguish the DC offsets directly, the proposed radar system is satisfied with equalizing both DC offsets for each of the two differential baseband signal pairs. Since the complex representation of the baseband signals is utilized for a subsequent arctangent demodulation, the proposed offset equalization implicates a centering of the in-phase and quadrature (I/Q) components of the received signal, which is sufficient to simplify the demodulation and improve the phase accuracy. Therefore, a standard Six-Port radar system is extended and a variable phase shifter plus variable attenuators are inserted at different positions. An intelligent algorithm adjusts these configurable components to achieve optimal I/Q offset cancelatio